PENYEDIAAN JARINGAN AIR BERSIH DARI MATA AIR KE LOKASI PEMUKIMAN DI DESA BINAFUN-KAB.KUPANG - Noni Banunaek; Yusuf Rumbino (Universitas Nusa Cendana, 2020)
East Nusa Tenggara Province only has a short rainy month and the rest of the dry season. So that water becomes the most important problem in this province. One of the government's efforts to overcome this problem is by utilizing groundwater basins through drilling activities. Community knowledge about groundwater management is still lacking, so education and assistance is needed regarding the governance of clean water facilities that will be provided by the government to the regions. The implementation team carries out community service along with an initial survey of the drilling location for groundwater which will be facilitated by the government. The method of activity applied is community education by providing residents with knowledge about the formation of groundwater and training to install / install water pipes, manufacture of water catchment tanks from springs and manufacture of reservoirs as water distributor tanks close to settlements. The benefit of this activity is that the community does not have to take water far from the spring, but it is sufficient to collect it from the distribution tub closest to the settlement